A multidisciplinary pulmonary embolism response team (PERT): first experience from a single center in Germany - Sagoschen, Ingo; Scibior, Barbara; Farmakis, Ioannis T.; Keller, Karsten; Graafen, Dirk; Griemert, Eva-Verena; Vosseler, Markus; Treede, Hendrik; Münzel, Thomas; Knorr, Maike; Gori, Tommaso; Konstantinides, Stavros; et al. (Clinical research in cardiology, 2024)
Over the last few years, the concept of multidisciplinary pulmonary embolism response teams (PERTs) has emerged to encounter the increasing variety and complexity in managing acute pulmonary embolism (PE).